Quale tutela per il lupo (canis lupus)? Il quadro normativo vigente e le possibili prospettive. - GARZIA, GIUSEPPE (2020)
In last few years the wolf population has greatly increased in Italy. This study is aimed at analyzing the national and international regulatery framework of the wolves protection and the jurisprudence of the Court of Justice. In this regards, two of the latest laws of 2018 – issued by the Autonomous Provinces of Trento e Bolzano – which allowed, in particular situations, the killing of wolves, will be examined in the light of the sentence of Corte Costituzionale n. 215 of 2019. Finally, possible legal tools will be selected in order to foster wolf-human coexistence